2017
DOI: 10.1055/s-0042-121667
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the safety of physician-directed nurse-administered propofol sedation in low-risk patients undergoing endoscopy and colonoscopy

Abstract: Background and study aims Physician-directed nurse-administered balanced propofol sedation (PhD NAPS) in patients undergoing endoscopy and/or colonoscopy is being increasingly utilized worldwide. However, this method of sedation is not universally employed in Australian hospitals due to concerns surrounding its safety. The aim of this study was to assess the safety of PhD NAPS in low-risk patients undergoing endoscopy and/or colonoscopy. Patients and methods This study was conducted at a single tertiary teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
(23 reference statements)
1
22
1
2
Order By: Relevance
“…Drug-induced hypoventilation may cause hypoxemia and carbon dioxide retention. Pulse-oximetry is a useful indicator of oxygenation (21). When propofol is administered concomitantly with an opioid, it causes less respiratory depression (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug-induced hypoventilation may cause hypoxemia and carbon dioxide retention. Pulse-oximetry is a useful indicator of oxygenation (21). When propofol is administered concomitantly with an opioid, it causes less respiratory depression (8).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a more profound fall in blood pressure may occur in the hypovolemic patient. Volume support can be beneficial; therefore, it can be suggested in order to prevent hypotension due to propofol (21).…”
Section: Discussionmentioning
confidence: 99%
“…Our argument is further supported by earlier studies that have shown that although propofol has a more rapid onset of action and shorter recovery time than do traditional sedatives, it does not improve other clinically important outcomes. [25][26][27] Although the present study is unique in that it explores the utility of adjunct sedatives in a difficult-to-sedate patient population, it is not without limitations. We recruited only veterans; therefore, the main limitation is that most of our patients were white males.…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple previous publications comparing an expanded class of AEs when using anesthesia, primarily with propofol assistance for endoscopic procedures compared with endoscopist-given sedation using midazolam and fentanyl. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In one, Cooper et al 6 reviewed a random sample of 5% of all Medicare patients undergoing colonoscopy without polypectomy in 1 of the regions served by the Surveillance, Epidemiology, and End Results registry. These authors reviewed 165,527 procedures, 21.2% of which were done with anesthesia services.…”
mentioning
confidence: 99%